The tribological behaviour of titanium alloys suitable for dental implants: A short review - Roegnitz Alexander; Haeger Andreas (Current Directions in Biomedical Engineering, 2024)
Titanium and its alloys play a vital role in dental implantology, providing a stable foundation for replacement teeth and restoring oral function effectively. Titanium alloys, particularly CP-Ti and Ti-6Al-4V, are widely utilized due to their biocompatibility, corrosion resistance and mechanical properties. However, concerns arise regarding the release of cytotoxic elements and stress shielding effects. Addressing these concerns requires advancements in material design and tribological properties. Research focuses on developing low modulus β-type Ti-based alloys with improved wear resistance and biocompatibility, incorporating elements like niobium, tantalum or zirconium. This review explores the tribological implications of these advancements, focussing on the implantabutment interface, emphasizing the need for optimized titanium alloys for dental implant applications.